2005
DOI: 10.1073/pnas.0502138102
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcription-associated dephosphorylation of hepadnavirus nucleocapsids

Abstract: Hepatitis B viruses are pararetroviruses that contain a partially dsDNA genome and replicate this DNA through an RNA intermediate (the pregenomic RNA, pgRNA) by reverse transcription. Viral assembly begins with the packaging of the pgRNA into nucleocapsids (NCs), with subsequent reverse transcription within NCs converting the pgRNA into the characteristic dsDNA genome. Only NCs containing this dsDNA (the so-called ''mature'' NCs) are enveloped by the viral envelope proteins and secreted as virions; ''immature'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
172
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(188 citation statements)
references
References 54 publications
14
172
2
Order By: Relevance
“…In fact, capsids from core protein variants lacking part of this region still package pgRNA but appear unable to produce full-length RC-DNA; instead they preferentially reverse transcribe the fraction of spliced genomic RNAs [46,47] . Phosphorylation/dephosphorylation events at the S and T residues in the nucleic acid binding domain clearly accompany genome maturation [48] , and mutations affecting the core phosphorylation status [46,49] can influence DNA synthesis in various ways. Outside capsids, or in the absence of core protein, apparently no full-length DNA can be formed.…”
Section: Tion Of Pgrnamentioning
confidence: 99%
“…In fact, capsids from core protein variants lacking part of this region still package pgRNA but appear unable to produce full-length RC-DNA; instead they preferentially reverse transcribe the fraction of spliced genomic RNAs [46,47] . Phosphorylation/dephosphorylation events at the S and T residues in the nucleic acid binding domain clearly accompany genome maturation [48] , and mutations affecting the core phosphorylation status [46,49] can influence DNA synthesis in various ways. Outside capsids, or in the absence of core protein, apparently no full-length DNA can be formed.…”
Section: Tion Of Pgrnamentioning
confidence: 99%
“…However, the S245A mutant was deficient in genome maturation [48] . It has been shown that the CTD contains several phosphosites, which are heterogeneously phosphorylated intracellularly and hypophosphorylated or non-phosphorylated in the secreted virion [40,43] . This dephosphorylation, which occurs as nucleocapsids mature (meaning that the pgRNA is reverse transcribed into the rcDNA genome), is thought to be a maturation signal that results in secretion of only fully matured virions containing the DNA genome [43] .…”
Section: Core Protein and E-antigenmentioning
confidence: 99%
“…It has been shown that the CTD contains several phosphosites, which are heterogeneously phosphorylated intracellularly and hypophosphorylated or non-phosphorylated in the secreted virion [40,43] . This dephosphorylation, which occurs as nucleocapsids mature (meaning that the pgRNA is reverse transcribed into the rcDNA genome), is thought to be a maturation signal that results in secretion of only fully matured virions containing the DNA genome [43] . In addition, it has been shown that binding of hepadnaviral capsids to the nuclear pore complex depends on the phosphorylation status of the core protein [35] .…”
Section: Core Protein and E-antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…When the polymerase reaches the 5' end of pgRNA, an RNA oligomer containing DR1 and the 6 to 7 nucleotides at the 5' end of DR1 sequence is left uncleaved. It is this RNA oligomer that is subsequently translocated and annealed to the direct repeat 2 (DR2) and primes plus strand DNA synthesis to yield relaxed circular DNA (rcDNA) [31].When rc DNA are formed, the nucleocapsids are matured and can be enveloped and secreted out of cells [49,50].…”
Section: Synthesis Of Progeny Viral Dna Genomes From Pgrna In the Cytmentioning
confidence: 99%